2017
DOI: 10.1097/scs.0000000000003173
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of a Bifid Mandibular Condyle in Dry Mandibles

Abstract: The established frequency of BMC was comparable with those reported in Turkish and Korean populations. The lack of injury marks and traces implies a developmental etiology of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…No age predilection exists. However, bifid condyle occurs in age groups of six to 35 years [ 4 ]. The study by Nikolova et al reported an incidence of unilateral bifid condyle observed in four (0.8%) of 500 dry mandibles, with two (0.4%) occurring in the right condyle and two (0.4%) occurring in the left condyle [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No age predilection exists. However, bifid condyle occurs in age groups of six to 35 years [ 4 ]. The study by Nikolova et al reported an incidence of unilateral bifid condyle observed in four (0.8%) of 500 dry mandibles, with two (0.4%) occurring in the right condyle and two (0.4%) occurring in the left condyle [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, bifid condyle occurs in age groups of six to 35 years [ 4 ]. The study by Nikolova et al reported an incidence of unilateral bifid condyle observed in four (0.8%) of 500 dry mandibles, with two (0.4%) occurring in the right condyle and two (0.4%) occurring in the left condyle [ 4 ]. The prevalence rate of bifid condyles, as studied from orthopantomography and cone-beam computed tomography of paranasal sinuses, was 3.5% and 4.53%, respectively [ 5 , 6 ] (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the meta-analysis of the prevalence of the BMC, 15 studies were included [16,17,[22][23][24][25]27,31,32,[35][36][37][38][39]47], with a prevalence of 1% with a deviation standard from 1 to 2%, showing a heterogeneity of (I 2 = 82%) (Table 3 and Figure 4). Regarding the risk of bias in the case studies, in a total of 11 studies, 100% of the articles analyzed presented a low risk of bias.…”
Section: Prevalence and Risk Of Biasmentioning
confidence: 99%
“…presented a high risk of bias in eight of the eleven articles analyzed [18][19][20][21]28,29,33,34,40,41,45] (Table 4 and Figure 5). For the analysis of biases using AQUA, 22 studies were included [16,17,[22][23][24][25][26][27][30][31][32][35][36][37][38][39]43,44,46,47], of which the main bias presented by the studies was the reporting of results in 7 of 21 studies, and the other items presented a low risk of bias (Table 5 and Figure 6).…”
Section: Prevalence and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation